A new heterometallic MOF with 1D nano-sized channels for cyanosilylation reaction and prevention effect against arrhythmia by reducing the sympathetic excitability. Issue 1 (1st January 2020) - Ding, Chao; Zhang, Weiwei; Xu, Zhenzheng; Zhang, Huimin; Zheng, Junqi
Abstract: In this work, by appealing to a heterometallic cluster approach, a new highly porous metal-organic framework (MOF) formulated as (Me2 NH2 )[Ni3 K2 (TZIA)3 (H2 O)3 ]·(DMF)4 n (1 ) has been fabricated by a solvothermal reaction of a bifunctional organic ligand 5-(1 H-tetrazol-5-yl)isophthalic acid (H3 TZIA) with the Ni(II) and K(I) salts in water and DMF mixed solvents. The resulting activated 1a has been explored in detail for BET analysis to probe its porosity. The removal of water molecule at the aim of generating 1a makes K + ion become a heterogeneous catalyst of size-selective with high efficiency for solvent-free cyanosilylation of acetaldehyde under mild conditions. Furthermore, the prevention effect of the compound on the arrhythmia occurrences after anesthesia during operation was evaluated. The arrhythmia incidence and abnormal blood pressure was calculated and measured for the detection of compound prevention ability. Besides, the Norepinephrine (NE) and Adrenaline (A) released by the cardiomyocytes were measured by the ELISA kit.